2016
DOI: 10.15406/jsrt.2016.01.00034
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Characterization and Differentiation Potential of Rat Bone Marrow derived Mesenchymal Stem Cells

Abstract: Abbreviations: rBM-MSC, rat bone marrow derived mesenchymal stem cells; CFU-F, colony forming unit-fibroblast; DPBS, dulbecco's phosphate buffer saline; DMEM, dulbecco's modified eagles medium; RT PCR, reverse transcription polymerase chain reaction; RNA, ribonucleic acid IntroductionBone marrow hosts variety of tissues including hematopoietic lineage cells and mesenchymal stem cells (MSCs). The hematopoietic cells are the major source of the blood cells in the adult body which are regulated within the microen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Flow cytometry analysis was performed to determine whether the preconditioning protocols with LPS or Poly(I:C) would change the expression of key cell surface markers used for the identification of the MSC phenotype. Cells were treated with LPS or Poly(I:C) or kept in control medium without stimulation for 1 h, washed, and allowed to grow for an additional 23 h. While CD90 and CD29, two MSC markers [38, 39], were expressed by more than 98% of the cells in all conditions (Figure 3), less than 4.12% of the cells expressed the hematopoietic lineage markers CD45 and CD34 in all experimental groups (Figure 3). In line with these results, we observed that the morphology of MSCs was not changed 23 h after the removal of LPS or Poly(I:C), as assessed by staining the cells with phalloidin for F-actin labeling (Figure 4(b)).…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometry analysis was performed to determine whether the preconditioning protocols with LPS or Poly(I:C) would change the expression of key cell surface markers used for the identification of the MSC phenotype. Cells were treated with LPS or Poly(I:C) or kept in control medium without stimulation for 1 h, washed, and allowed to grow for an additional 23 h. While CD90 and CD29, two MSC markers [38, 39], were expressed by more than 98% of the cells in all conditions (Figure 3), less than 4.12% of the cells expressed the hematopoietic lineage markers CD45 and CD34 in all experimental groups (Figure 3). In line with these results, we observed that the morphology of MSCs was not changed 23 h after the removal of LPS or Poly(I:C), as assessed by staining the cells with phalloidin for F-actin labeling (Figure 4(b)).…”
Section: Resultsmentioning
confidence: 99%
“…Any excess stain was washed away with distilled water. The colonies were observed and macroscopically counted on the 24-well plates ( Paramasivam et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow was obtained from femur and tibia of adult wistar rat. Isolation, expansion, characterization and differentiation studies were performed as per the protocol developed in our lab [21,22]. The 3rd passage rat bone marrow mesenchymal stem cells (rBMSC) were used after attaining 40-80% confluence.…”
Section: Transfection Of Pvax1-pdgf-b Gene Plasmid With Rbmscmentioning
confidence: 99%